2023
DOI: 10.1093/rap/rkad109
|View full text |Cite
|
Sign up to set email alerts
|

First contact physiotherapists: are they able to reduce the burden on rheumatology services? A critical review of the evidence base

Sarah R Golding,
Jo Jackson

Abstract: First Contact Practitioners have emerged over recent years in response to growing pressures within the National Health Service (NHS) and are now central to primary care musculoskeletal (MSK) services. Within the musculoskeletal field these allied health professionals may be from a range of disciplines including Physiotherapy, Podiatry and Osteopathy. Early referral to rheumatology is key to successful long-term management of many inflammatory musculoskeletal conditions but presents challenges to overburdened s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In this issue of Rheumatology Advances in Practice , Golding and Jackson [ 4 ] present a critical review of the evidence base for the FCP role in rheumatology, while reviewing the emerging themes within the MSK field as a whole. Given the large number of FCPs funded and established in NHS primary care positions, this role must be embraced by those of us in rheumatology as we seek to improve the efficiency of rheumatology services with regards to incoming referrals [ 5 ].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue of Rheumatology Advances in Practice , Golding and Jackson [ 4 ] present a critical review of the evidence base for the FCP role in rheumatology, while reviewing the emerging themes within the MSK field as a whole. Given the large number of FCPs funded and established in NHS primary care positions, this role must be embraced by those of us in rheumatology as we seek to improve the efficiency of rheumatology services with regards to incoming referrals [ 5 ].…”
mentioning
confidence: 99%
“…Given the large number of FCPs funded and established in NHS primary care positions, this role must be embraced by those of us in rheumatology as we seek to improve the efficiency of rheumatology services with regards to incoming referrals [ 5 ]. Despite the dearth of application research found in the Golding and Jackson article [ 4 ], frameworks of practice for FCPs do demonstrate good representation of inflammatory condition screening [ 6 ], and the Rheumatology Physiotherapy Capabilities Framework [ 7 ] has a section of capabilities statements dedicated specifically to this role of FCPs, shown in Fig. 1 .…”
mentioning
confidence: 99%
See 3 more Smart Citations